El papel de la educación en el proyecto político del catalanismo ultramarino: la revista Ressorgiment de Buenos Aires durante la primera mitad del siglo XX - Marcela Lucci (Amnis)
With reference to the journal Ressorgiment, we analyse the contributions made by Buenos Aires-based Catalan separatism in the attempt to implement—within Catalonia— an education system in Catalan. We study the publication’s editorial policy and approach, which favored providing Catalan schools with a pedagogical renovation capable of reproducing national identity and of responding successfully to the needs of society at the outset of the twentieth century.